Home goods and regional price indices: A perspective from New Economic Geography - Jens Südekum (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2001)
In standard models of New Economic Geography the overall regional price index in the centre is lower than in the periphery, because trade in manufacturing imposes transportation costs whereas trade in agriculture is assumed to be costless. Since real world observations suggest higher overall CPIs in the centre than in the periphery, this paper presents a model where a home goods sector is added. The model is able to explain a sustainable core-periphery structure with higher aggregate CPI in the centre. This structure can emerge endogenously out of the system itself and does not need to exist initially. Hence, the standard model of New Economic Geography can gain realism by the modification proposed in this paper.
Keywords: 330; Räumliche Preistheorie; Regionale Preisstruktur; Kern-Peripherie-Beziehung; Nicht-handelbares Gut; Räumliche Gleichgewichtstheorie; Theorie; Neue ökonomische Geographie